2012
DOI: 10.1021/mp200523n
|View full text |Cite
|
Sign up to set email alerts
|

Oral Gene Delivery with cyclo-(d-Trp-Tyr) Peptide Nanotubes

Abstract: The feasibility of cyclo-(D-Trp-Tyr) peptide nanotubes (PNTs) as oral gene delivery carriers was investigated in nude mice with eight 40 μg doses of pCMV-lacZ in 2 days at 3 h intervals. The association between DNA and PNTs, the DNase I stability of PNTs-associated DNA, and in vitro permeability of DNA were estimated. The results showed that the cyclo-(D-Trp-Tyr) PNTs self-associated at concentrations above 0.01 mg/mL. Plasmid DNA associated with PNTs with a binding constant of 3.2 × 10 8 M −1 calculated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(95 citation statements)
references
References 87 publications
4
90
1
Order By: Relevance
“…Figure 2 outlines the synthesis of the CP-polymer conjugates, which can be achieved via two synthetic pathways; (i) coppercatalysed azide-alkyne cycloaddition/thiol-ene (CuAAC/thiolene) or (ii) thiol-ene/CuAAC. The first step in the CuAAC/ thiol-ene pathway involved the conjugation of an alkyneterminated PBA or PCHA to the azidolysine side chain of 2 via microwave-assisted CuAAC to yield a one-armed CP-polymer intermediate (3)(4)(5)(6)(7). Microwave-assisted CuAAC has previously been shown to yield high conversions for CP-polymer conjugates using 10 mol% excess polymer relative to the CP bearing two azidolysine residues 24,26 .…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 outlines the synthesis of the CP-polymer conjugates, which can be achieved via two synthetic pathways; (i) coppercatalysed azide-alkyne cycloaddition/thiol-ene (CuAAC/thiolene) or (ii) thiol-ene/CuAAC. The first step in the CuAAC/ thiol-ene pathway involved the conjugation of an alkyneterminated PBA or PCHA to the azidolysine side chain of 2 via microwave-assisted CuAAC to yield a one-armed CP-polymer intermediate (3)(4)(5)(6)(7). Microwave-assisted CuAAC has previously been shown to yield high conversions for CP-polymer conjugates using 10 mol% excess polymer relative to the CP bearing two azidolysine residues 24,26 .…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The simplicity of this bottom-up approach together with the resultant uniformity and size of the self-assembled nanoscopic structures provides an attractive strategy, which favours applicability in the field of nanoscience and nanotechnology 5 . Among the different types of self-assembled architectures, nanotubular structures have gained considerable interest because of their suitability for various applications including nanomedicine 6,7 , (bio)sensing 8,9 , separation and recovery technologies 10 as well as nanoelectronics 11 . A distinct feature of tubular structures that is often absent from traditional self-organized supramolecular structures for example, micelles and vesicles, is the internal channel cavity, which in the case of self-assembled nanotubes (NTs) has a defined diameter that can provide a means for selective transport or molecular encapsulation properties.…”
mentioning
confidence: 99%
“…Ding et al A couple of studies of drug-loaded ONTs in animals have also been reported for oral gene delivery, 19 intravitreal delivery of anticancer drugs, 20 and intravenous delivery of irinotecan. 21 An ONT with a length of 2 µm outer diameter of 70-90 nm was found to accumulate specifically in the lung and be quickly cleared from blood circulation.…”
mentioning
confidence: 99%
“…Among the most researched on are those that are highly responsive to the external stimuli. A wide range of polymeric nanomaterials carrying smart switchable components has been developed over the decades [1][2][3][4][5][6][7]. For example, multistimuli responsive nanomaterials based on amphiphilic polymer composites containing hydrophilic and lipophilic macromers with environment-sensitive micellar properties have been reported [8].…”
Section: Introductionmentioning
confidence: 99%